An introduction to the philosophy of art - Eldridge, Richard (Cambridge University, 2013)
In this book Richard Eldridge presents a clear and compact survey of philosophical theories of the nature and significance of art, drawing on materials from classical and contemporary philosophy as well as from literary theory and art criticism.